Do fish have rights in artisanal fisheries? - Moshood Mustapha (Journal of Tropical Life Science, 2013)
Artisanal fishers in developing world are unaware that fish are capable of suffering or discomfort, though researches have shown that fish do feel pain. Five fish welfare domains have been identified which constitute their rights in their environment. The needs of wild fish are usually provided in their natural, undisturbed and unperturbed aquatic environment, of which the fish will prefer. However, various anthropogenic activities by humans (including artisanal fisheries itself) and some natural perturbations in the watershed, riparian zone, water body of the fish habitat and on the fish tend to take away these needs thereby compromising the fish welfare. These activities include environmental degradation, boat/canoe building, use of motorized engine boats/canoes, use of active and passive fishing gears, obnoxious cultural, religious and social fishing practices, fish harvesting, handling and processing among others. One way to understand the welfare needs of an individual fish is to understand its biology. Poor welfare conditions could then be assessed by how far the individual fish has deviated from the normal conditions. Non-intrusive signs based on the health, behavior, morphological anomalies, swimming, reduction in population and growth, outbreak of parasitic infections, injuries and loss of condition can be used to assess fish whose welfare has been compromised. Artisanal fishers should not only be concerned with catch, but, also the welfare of the fish being caught. This is because if the welfare of the fish is compromised, it is going to definitely affect the catch. As indispensable as fish is to humans, humans should not derive its pleasure at the expense of fish suffering. Human activities that impinge on the welfare of wild fish may not necessarily be stopped, but at least minimized in order to have continued sustainable artisanal exploitation of the fisheries. Keywords: welfare, artisanal fisheries, developing world, stress, behaviour, feel, habitat